RESILIENSI SEBAGAI MEDIATOR HUBUNGAN SELF-COMPASSION DENGAN STRES PENGASUHAN PADA IBU BEKERJA - Wahyuni, Citra; Syafitri, Artika; Isnaeni, Ahmad; Rizkyanti, Charyna Ayu (Inquiry: Jurnal Ilmiah Psikologi, 2024)
Parenting stress is an uncomfortable and unpleasant condition experienced by parents when raising children. This study aims to determine the mediating role of resilience in the relationship between self-compassion and parenting stress in working mothers. This study uses a quantitative correlational design method with a sampling technique used is purposive sampling, so that a sample of 86 working mothers with children aged 0-6 years was obtained. The data collection technique uses three scales, namely the self-compassion scale, the resilience scale, and the parenting stress scale. The analysis technique in this study uses effect mediation analysis, multiple regression, and correlation. The results showed that resilience acts as a partial mediator in the relationship between parenting stress and self-compassion with an estimate value of -0.046, p <0.01. The results also show a value of r = -0.640, p <0.01, which means that there is a significant negative relationship between self-compassion and parenting stress. Then the results show a value of r = -0.630 p <0.01, which means that there is a significant negative relationship between resilience and parenting stress. The results of the study indicate that resilience partially mediates the relationship between self-compassion and parenting stress. This means that there are other variables that can mediate the relationship between self-compassion and parenting stress, and self-compassion and resilience are needed in working mothers who have children aged 0-6 years to cope with stress that arises in parenting.